Aktivitas Antibakteri Propionibacterium acnes Ekstrak Bunga Kenanga (Cananga odorata) Terhadap Variasi Jenis Pelarut dan Waktu Maserasi - Sinaga, Reni; Anggreni, Anak Agung Made Dewi; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Ylang ylang flower is one of the natural sources that contain antibacterial compounds. One of the bacterial infections on the skin surface is acne and is aggravated by the existence of Propionibacterium acnes bacteria. This experiment aims to determine the effect of solvent type and maceration time on the effectiveness of ylang flower extract in inhibiting P.acnes bacteria, and to determine the combination of solvent type and maceration time that produces ylang flower extract with the best antibacterial activity. This experiment used Factorial Randomised Group Design (RAK) with two factors. The first factor is the solvent type which includes ethanol, methanol, and n-hexane. The second factor is maceration time which includes 24, 48, and 72 hours. The variables observed in this study included yield, total phenol, and the highest antibacterial activity. The obtained data were then analysed with analysis of variance (ANOVA), then continued with Duncan's test. The results of this study showed that the type of solvent and maceration time significantly affected the yield, total phenol, and antibacterial activity on P.acnes test bacteria. The interaction between treatments had a significant effect on yield but no significance on total phenol and antibacterial activity on P.acnes test bacteria. The best solvent type that can produce kenanga flower extract with the highest antibacterial activity is methanol with an inhibition zone of 8.48 ± 1.66 mm, with yield of 5.03 ± 0.10% and total phenol of 43.04 ± 0.81 mg GAE/g. The best maceration time that can produce kenanga flower extract with the highest antibacterial activity is 48 hours with an inhibition zone of 5.35 ± 0.79 mm, with yield of 5.03 ± 0.10% and total phenols of 31.69 ± 1.27 mg GAE/g.